Serological Study for Celiac Disease among Sample of Iraqi Patients - Mohammed waheed; Amina N. AL-Thwani; Rabab Q. AL-Segar (مجلة مركز بحوث التقنيات الاحيائية, 2017)
This study aimed to detect the celiac disease by using serological markers including AGA and Ttg. Celiac disease (CD) is a complex small intestinal disorder due to a dysregulated immune response to wheat gliadin in children and adults. A total of 412 suspected patients with celiac disease of males and females with age rang (1-48) year, attended Central Public Health Laboratory (CPHL) Baghdad/ Iraq during the period between December 2015 - April 2016, only fifty patients with celiac disease with age rang 1-40 were confirmed by two serological test which were Anti-gliadin antibodies (AGA) and Anti-Tissue transglutaminase (tTG) conducted by ELISA. The results, showed that 73 (17.72 %) of patients were seropositive AGA-IgA, and 83 (20.15%) were seropositive for AGA-IgG, whereas 67 (16.27%) were seropositive for both IgA and IgG of AGA test. The seropositive patients for tTG- IgA and tTG -IgG were 60 (14.56 %), and 69 (16.75 %) respectively. The seropositive for both (tTG -IgA and IgG) represented 53 (12.87 %) patient.